Pengembangan Backend Aplikasi Geoproperty dengan Golang di PT. Nerdvana Solusi Teknologi - Ramdani, Muhammad Asnur; Nabarian, Tifanny; Maulana, Reza (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
This research discusses the backend design of the Golang-based GeoProperty application at PT Nerdvana Solusi Teknologi, which is designed to improve the property search experience with the integration of Geographic Information System (GIS) technology. This research focuses on developing the backend using the Agile Scrum method to ensure optimal functionality in managing spatial and property data. The backend supports key features such as interactive map-based property search, polygon input for search area boundaries, and Point of Interest (POI) visualization around the property. Testing was conducted using the blackbox testing method to evaluate API functionality. The results show that the backend system can meet user needs with reliable performance, provide accurate visualization of property locations, and comprehensive information that supports prospective buyers' decisions.